Fabrication of doped β-tricalcium phosphate bioceramics by Direct Ink Writing for bone repair applications. Issue 2 (February 2023) - Somers, Nicolas; Jean, Florian; Lasgorceix, Marie; Preux, Nicolas; Delmotte, Cathy; Boilet, Laurent; Petit, Fabrice; Leriche, Anne
Abstract: β-tricalcium phosphate (β-TCP, β-Ca3 (PO4 )2 ) is one of the most attractive biomaterials for bone regeneration and β-TCP macroporous scaffolds are very promising for both cell proliferation and mechanical support. The Additive Manufacturing (AM) process called Direct Ink Writing (DIW), based on the extrusion of a concentrated ceramic slurry, is particularly adapted to resolve the main drawbacks associated with conventional shaping of ceramic scaffolds. In this work, co-doped β-TCP powders were synthetized and used to print macroporous scaffolds by DIW. Doped β-TCP powders have been proved to exhibit higher thermal stability, densification and mechanical properties compared to undoped β-TCP. Two co-doped compositions were produced via the aqueous precipitation technique combining magnesium, strontium, silver and copper cations: Mg-Sr (2.0–2.0 mol%) and Mg-Sr-Ag-Cu (2.0–2.0–0.1–0.1 mol%). DIW slurries were optimized with undoped and co-doped β-TCP with the use of a dispersant and a carboxymethylcellulose and polyethyleneimine mixture to obtain aqueous slurries filled with 42 vol% of powder. Complete rheological characterizations were realized to assess the suitability of the β-TCP slurries for the DIW process (shear-thinning and thixotropic behaviour). The whole processing chain including printing, osmotic drying (PEG 10000) and sintering (1100 °C, 3 h) was optimized to successfully print co-doped β-TCP macroporous scaffolds. Characterizations after sintering showed a reduction of macropores and microcracks using co-doped β-TCP powders as well as improved compressive strengths and densities compared to undoped β-TCP. A significant enhancement of compressive strength values was obtained compared to literature data.